REDUCTION OF TERM MATRIX OF CONTROL UNIT WITH CODE SHARING - Barkalov, А. А.; Zeleneva, I. Y.; Tsololo, S. A.; Biairak, H. (Radio Electronics, Computer Science, Control, 2012)
The structures of compositional microprogram control unit with code sharing are proposed. Structures allow reducing the complexity of the matrix realization in the device’s circuit. The proposed method is based on using of node’s address representation as a concatenation of OLC codes and code of OLC components. The proposed method allow reducing the complexity of the matrix realization in the device’s circuit.